Stress Level Of Pregnant Women During The Pandemic Covid-19 - Wibowo, Dodik Arso; Muchsin, Enur Nurhayati (Journal of Applied Nursing and Health, 2023)
PlagueCorona Virus Disease 2019 (Covid-19) makes everyone stressed and anxious because the transmission is very fast. Pregnant women during the Covid 19 pandemic do not rule out the possibility of experiencing stress due to the fear that something will happen to their pregnancy. Pregnancy with high stress levels can certainly have a negative impact on the mother and fetus. Stress is the body's non-specific response to every load demand and general reaction patterns and adaptations. Proper handling of pregnant women by the family can reduce the level of stress experienced by pregnant women. The purpose of this study was to determine the Stress Level of Pregnant Women During the Covid-19 Pandemic in Kalianyar Village, Ngronggot District, Nganjuk Regency. Descriptive research design, population and sample of 25 respondents with a sampling technique "total sampling”. The research was conducted on December 15-26 2020, the research variable Stress Levels for Pregnant Women during the Covid-19 Pandemic as a questionnaire research instrument, was analyzed by percentage and interpreted quantitatively. The research results obtained from 25 respondents, almost all respondents experienced moderate stress as many as 20 respondents (80%). A small portion of the respondents experienced severe stress as many as 5 respondents (20%). This is influenced by several factors, namely: age, education, occupation, history of pregnancy, gestational age, information about Covid-19, sources of information about Covid-19, and history of pregnancy examinations (ANC). It is hoped that pregnant women can control stress, get support from their families, always implement health protocols and think positively during pregnancy during the Covid-19 pandemic.